A Study of Risk Behaviors in Substance Use among Vocational Certificate Students in an Educational Institution in the Peri-Urban Area - Thanasap, Napat; Trimek, Jomdet (Journal of Dhamma for Life, 2025)
This research aimed to investigate the causes of risk behaviors related to substance use among vocational certificate (Por Wor Chor) students in an educational institution located in a peri-urban area. Another objective was to synthesize relevant theoretical concepts and formulate comprehensive strategies for prevention and intervention. This study adopted a qualitative research design, utilizing in-depth interviews as the primary method for data collection. The key informants included 11 third-year students in the academic year 2025 and 4 educational personnel totaling 15 participants. Empirical data were obtained via in-depth interviews and subsequently analyzed using content analysis. The research findings revealed the following guidelines for preventing and addressing substance use risk behaviors among vocational students: 1) educational institutions should establish an anti-drug policy; 2) provide ongoing education on the dangers and legal aspects of drug use to students personnel parents and the community; 3) organize awareness-raising activities on designated awareness days complemented by the integration of substance use education into the curriculum; 4) develop a student support system that includes risk group identification regular urine drug testing at least once a year and home visits; 5) encourage teachers and parents to closely observe and support students' behavior; 6) collaborate with law enforcement experts and community leaders to prevent student involvement in harmful social behaviors; and 7) maintain a clean safe and orderly school environment conducive to learning. The study highlights that a comprehensive and collaborative approach involving schools, families, and communities is essential for effectively preventing and mitigating substance use among vocational students.